2022
DOI: 10.3390/life12071034
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Ischemia Related to Common Cancer Therapy—Prevention Insights

Abstract: Modern antineoplastic therapy improves survival and quality of life in cancer patients, but its indisputable benefits are accompanied by multiple and major side effects, such as cardiovascular ones. Endothelial dysfunction, arterial spasm, intravascular thrombosis, and accelerated atherosclerosis affect the coronary arteries, leading to acute and chronic coronary syndromes that negatively interfere with the oncologic treatment. The cardiac toxicity of antineoplastic agents may be mitigated by using adequate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 195 publications
(234 reference statements)
0
1
0
Order By: Relevance
“…Cancer is highly prevalent in the elderly, and cardiac toxicity of antineoplastic agents is currently a topic of major interest. Badescu et al have shown that some commonly used oncological treatments have adverse effects on coronary arteries, as they induce endothelial dysfunction, coronary artery spasm, thrombosis, and fibrosis [ 6 ]. These harmful structural and functional changes lead to cardiovascular events that require reduction or temporary or permanent stop of antineoplastic therapy, and all of these events have a negative impact on cancer outcomes.…”
mentioning
confidence: 99%
“…Cancer is highly prevalent in the elderly, and cardiac toxicity of antineoplastic agents is currently a topic of major interest. Badescu et al have shown that some commonly used oncological treatments have adverse effects on coronary arteries, as they induce endothelial dysfunction, coronary artery spasm, thrombosis, and fibrosis [ 6 ]. These harmful structural and functional changes lead to cardiovascular events that require reduction or temporary or permanent stop of antineoplastic therapy, and all of these events have a negative impact on cancer outcomes.…”
mentioning
confidence: 99%